Factors Associated With Severe Nonmeningitis Invasive Pneumococcal Disease in Adults in France. (30th November 2019) - Danis, Kostas; Varon, Emmanuelle; Lepoutre, Agnès; Janssen, Cécile; Forestier, Emmanuel; Epaulard, Olivier; N'guyen, Yohan; Labrunie, Anaïs; Lanotte, Philippe; Gravet, Alain; Pelloux, Isabelle; Chavanet, Pascal; et al.
Abstract: Background: In France, pneumococcal vaccination in adults is recommended for risk groups (chronic conditions/immunosuppression). We conducted a study on invasive pneumococcal disease (IPD) in adults to identify factors associated with disease severity and death. Methods: We included IPD cases, excluding meningitis, from 25 acute care hospitals in 6 regions. We defined severe cases as those with shock or severe sepsis or intensive care unit admission/mechanical ventilation. We included deaths occurring within 30 days of hospitalization. Infectious disease specialists collected clinical/microbiological data on cases. Results: During 2014–2017, 908 nonmeningitis IPD cases were diagnosed; 48% were severe, 84% had comorbidities, 21% died. Ninety percent of cases with comorbidities who previously sought health care were not vaccinated against pneumococcus. Compared with previously healthy cases, the risk of severe IPD increased from 20% (adjusted risk ratio [aRR], 1.2; 95% confidence interval [CI], 1.0–1.4) in cases with 1–2 chronic diseases to 30% (aRR, 1.3; 95% CI, 1.0–7.0) in those with >2 chronic diseases. Among risk groups, 13-valent pneumococcal conjugate vaccine (PCV13) serotypes and 23-valent pneumococcal polysaccharide vaccine (PPSV23) nonPCV13 serotypes were more likely to induce severe IPD compared with nonvaccine serotypes (aRR, 1.5; 95% CI, 1.3–1.9; aRR, 1.3; 95% CI, 1.0–1.5, respectively). Conclusions: We observed a cumulative effect of concurrent comorbidities on severe IPD. Vaccine serotypes were more likely to induce severe IPD among risk groups. The missed opportunities for vaccination underscore the need to enhance vaccination in risk groups.